Negotiating the global : how young women in Nairobi shape their local identities in response to aspects of the mexican telenovela, Cuando seas mia - Jiwaji, Aamera Hamzaali (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
Latin American telenovelas have been exported to more than a hundred countries across the globe. While they are popular in their country of production because their messages resonate with their audience's everyday experiences, their popularity amongst global audiences with whom they share neither a social nor a cultural history is unexplained. Kenya has been importing and airing Latin American telenovelas since the early 1990s, and telenovelas have permeated many aspects of Kenyan daily life, when compared to other foreign globally-distributed media products that are aired on Kenyan television. As global media products, telenovelas remain open to criticisms from the media imperialism thesis. This research adopts an ethnographic approach to the study of audiences, and looks at the reception of a Mexican telenovela, Cuando Seas Mia, by a group of young Kenyan women in Nairobi. It reflects upon the media imperialism thesis from an African perspective by investigating the meanings that these women make from Cuando Seas Mia, and how these shape their changing local identities and cultures. The young women in this study, most of whom have moved to the city from the rural areas, are influenced by traditional, patriarchal Kenyan society and by the modern, Western influences of an urban environment. They experience a tension between their evolving rural and urban roles and identities and are drawn to telenovelas because their exploration of rural-urban themes holds a relevance to their own lives. They negotiate their contemporary African youth identities, gender roles and heterosexual relationships in relation to representations in the telenovela, questioning and destabilising African and Western definitions. These women select aspects from their traditional, African cultures and from their modern, Western experiences (and consumption of global media) and reconstruct them into a transitional youth identity which suits their day to day lives as young women living in an urban African environment.
Keywords: Cuando seas mia (Television program); Television soap operas -- Kenya; Motion pictures and youth -- Kenya; Emigration and immigration in motion pictures -- Kenya; Ethnicity in motion pictures -- Kenya; Arts and society -- Kenya